Judicial Reasoning in Murabahah Disputes: A Maqashid al-Shariah Analysis of Religious Court Decision No. 7/Pdt.G.S/2024/PA.Jr - Reyhan, Muhammad Reyhan; Isman, Isman; Irkham Firdaus, Muhammad; Abdul Jalal, Ridwan (Universitas Islam Negeri Raden Intan Lampung, 2025)
The enactment of Law Number 3 of 2006 brought significant changes to the authority of the Religious Courts in handling Sharia economic disputes, including murabahah contracts. However, the application of Sharia principles in the decisions is still weak, mainly because the judges' legal reasoning tends to rely on positive law without considering fiqh muamalah. This research aims to analyse legal reasoning in the Jember Religious Court Decision Number 7/Pdt.G.S/2024/PA.Jr. and to assess the extent to which the principles of maqashid al-syariah are accommodated in resolving murabahah disputes. Unlike previous research that focused on the application of positive law, this study offers novelty by using the framework of maqashid al-syariah to assess the balance between formal legality and substantive justice. The method used is a juridical-normative approach through qualitative analysis of decision documents, DSN-MUI fatwas, and Sharia economic law literature. The research results indicate that judges emphasise positive law more, particularly Article 1243 of the Civil Code, without examining the validity of the contract based on Islamic jurisprudence and without referring to the fatwa of the National Sharia Council-Indonesian Ulema Council (DSN-MUI). Therefore, although the decision meets administrative aspects, its sharia law substance has not been fully realised. A more contextual and maqashid al-syariah-based legal approach is needed to achieve substantive justice in Islamic economic disputes.